Estimation of the individuality of the palatal rugae pattern. Issue 1 (2nd January 2021) - Syed, Sadatullah; Alshahrani, Ibrahim; Shiblee, Mohammed; Aseere, Ali M.; Dawasaz, Ali Azhar; Togoo, Rafi Ahmad
ABSTRACT: Although the palatal rugae pattern (PRP) is unique, it is not used in automated biometric systems such as fingerprints and irises. The aim of this study was to identify PRP parameters and formulate a model that determines the probability of correspondence (PC) of the PRP. In all, 154 dental casts were scanned in 3D, and the number of rugae, their characteristics, strength and area of the palate were recorded. With these parameters, a statistical model was developed and the PC of the PRP was calculated. For a palate with six rugae and an average palatal area of 1453.9 mm 2, the PC of the PRP is 1.29 × 10 –74, which is very low. Therefore, the PRP is unique and has an enormous amount of discriminatory information that can be useful for automated biometric systems in forensics and human identification.